PENGARUH KOMBINASI PENGATURAN POLA DIIT DM DAN SENAM DIABETES TERHADAP KADAR GULA DARAH PADA PASIEN DM TIPE II - Ni Made Risma Widyastuti (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2015)
Diabetes Mellitus is a disease that threatening human health and large number of diabetes mellitus patient keep on bigger every moment. Patients with diabetes mellitus tend to have problems with blood sugar metabolism that can cause various complications that can be short term and long term complications. The complications of Diabetes Mellitus due to abnormal blood sugar such as hyperglycemia, hypoglycemia and the long term complications of abnormal blood sugar can cause Cardiovascular diseases, Diabetic nephropathy, neuropathy Diabetic and retinopathy Diabetic. The purpose of this study was to identify the effect of combination Settings DM Diet and Diabetes Exercise on Blood Sugar Levels in Patient with Diabetes Mellitus Type II. This study used quasi experimental design with nonequivalent control group approach which consist of two groups : intervention group and control group with 18 samples in each group, using purposive sampling technique. After data collection, the data were analyzed by computer’s program with 95% confidence level. Pretest and posttest calf circumference data of intervention group and control group were analyzed by Shapiro Wilk and the result all data were normally distributed and analysis can proceed with parametric test. The result of paired t-test in intervention group showed a significant difference that the significant value is 0,000 while the result of the control group showed no significant difference with significant value 0,136. Independent sample t-test of intervention group and control group showed the diversification of intervention group and control group with significant value 0,002, thus it can be concluded that there are effect of combination Settings DM Diet and Diabetes Exercise on Blood Sugar Levels in Patient with Diabetes Mellitus Type II.